Empowerment of volunteer nursing service providers during disasters: A qualitative study - Mostafa Roshanravan; Shandiz Moslehi; Hesam Seyedin (BMC Emergency Medicine)
Abstract Background Volunteers providing nursing services are among the first individuals to arrive at the scene after an incident; therefore, they must use their skills and capabilities to provide necessary care for the injured to prevent problems from worsening and complications from arising. Consequently, having structured empowerment courses for volunteers before disasters seems essential. This research aimed to determine the dimensions and components of empowering volunteer nursing service providers in disasters. Methods This qualitative study was conducted using a conventional qualitative content analysis approach. Purposeful sampling with maximum variation continued until data saturation was achieved. The participants in this study were 25 individuals. Data collection was performed using semi-structured interviews. The conventional content analysis approach by Graneheim and Lundman was utilized for data analysis. After each interview, the text was entered into MAXQDA software version 2020, and semantic units were identified and coded, with codes categorized based on their similarities. To ensure the data’s trustworthiness, we applied key criteria including credibility, dependability, confirmability, transferability, and Authenticity throughout the research process. Results Among the 25 participants, 16 were male, and nine were female. The Mean age was 45.2 ± 5.6 years, and the Mean work experience was 19.08 ± 4.5 years. After coding the interviews, 253 initial codes were extracted. By merging these codes, 43 subcategories, 15 categories, and six themes were identified. Extracted themes include Infrastructure Initiatives, Effective management, Research development and knowledge management, Cultural Action Measures, Policymaking and legal affairs, Individual Competency Areas. Conclusions This study highlights the various dimensions and components that empower volunteers providing nursing services during disasters. Training and coordination between nursing managers and other leaders in health sectors are needed to ensure that these volunteers are equipped to provide frontline care in emergencies. Healthcare managers and policymakers can use this study’s results to create supportive legislation and training programs to enhance the capabilities of volunteer nursing providers in disasters.